PENGARUH BRAND EQUITY, DISPLAY PRODUCT DAN SERVICE QUALITY TERHADAP LOYALITY MELALUI PURCHASE DECISION SEBAGAI VARIABEL INTERVENING PADA UMKM BUKET BUNGA FLOW DI SITUBONDO - Pratiwi, Choliefiah Dwi; Fandiyanto, Randika; Ediyanto, Ediyanto (Fakultas Ekonomi dan Bisnis, 2025)
This study aims to analyze the effect of brand equity, display product, and service quality on loyalty with purchase decision as an intervening variable on Buket Bunga Flow UMKM in Situbondo. The research method used is quantitative with a descriptive and verification approach. Data were collected through questionnaires distributed to 90 Buket Bunga Flow consumer respondents and analyzed with the help of SmartPLS. The hypothesis testing using SmartPLS 3.2.8 reveals the following: brand equity has a significantly positive impact on purchase decision; product display has a significantly negative impact on purchase decision; and service quality positively and significantly influences purchase decision. Meanwhile, brand equity shows a positive but statistically insignificant effect on loyalty; product display has a significantly positive effect on loyalty; and service quality again shows a positive yet insignificant effect on loyalty. Furthermore, purchase decision has a positive but insignificant effect on loyalty. As for the indirect effects through purchase decision: brand equity shows a positive but insignificant effect on loyalty; product display has a negative but insignificant impact; and service quality exhibits a positive but insignificant effect.